Influence of Education Sources on Osteoporosis Knowledge and Calcium Intake in Adult Women: A cross sectional Study - Amanda Unanski Enright; Yeon K. Bai (International Journal of Nutrition, 2014)
Osteoporosis prevention among women requires obtaining proper knowledge early in life about the disease, risk factors and treatments. This study compares specific education sources to osteoporosis knowledge and calcium intake. Online survey usinga convenience sampling was performed with women between ages 18 and 40. The survey measured osteoporosis knowledge, calcium consumption, and specific education source within categories of age, school classes, television, radio, newspaper, magazine, Internet, and in-person. Multiple regression analysis determined influential education sources for osteoporosis knowledge and calcium intakes. Osteoporosis knowledge was suboptimal (13.8 ± 3.3, as a score higher than 16 defined as “adequate”) and average daily calcium intake was 1315.1 ± 609.9 mg. Age and newspaper had greatest contribution towards osteoporosis knowledge, while Internet, school classes and radio were most influential resources on calcium intakes. Creating an osteoporosis education initiative utilizing these sources is imperative for increasing disease knowledge and preventive behavior among young women.
Keywords: Osteoporosis